Knowledge and status of Hepatitis B vaccination among the newly admitted MBBS students in Chittagong Medical College (Journal of Chittagong Medical College Teachers' Association, 2009)
doi: 10.3329/jcmcta.v18i1.3813Journal of Chittagong Medical College Teachers' Association 2007: 18(1):9-11